Epistemological Foundations of Critical Rationalism in Modern Higher Education: Re-evaluating Karl Popper’s Educational Concept (MMIT Proceedings, 2026)
This paper revisits Karl Popper’s philosophy of critical rationalism and examines how its core epistemological principles — falsifiability, conjecture-and-refutation, and the rejection of justificationism — can be meaningfully applied to contemporary higher education. Rather than treating Popper as a historical artifact of mid-twentieth-century philosophy of science, the article argues that his ideas speak directly to unresolved tensions in how universities conceptualize knowledge, authority, and the purpose of teaching. Drawing on Popper’s major works alongside relevant secondary scholarship, the paper considers the genuine strengths and real limitations of a Popperian pedagogy. It concludes that critical rationalism offers a distinctive and underused resource for rethinking the epistemological culture of universities — one that grows more rather than less pertinent given the current climate of epistemic confusion in public life.
Keywords: Karl Popper; critical rationalism; falsifiability; higher education; epistemology; pedagogy; open society